PERAN PEMBERDAYAAN KARYAWAN DALAM MEMEDIASI HUBUNGAN ANTARA GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA KARYAWAN - Paradisani, Putu Tera; Putra, Made Surya (E-Jurnal Manajemen; Vol 8 No 9 (2019), 2019)
The purpose of this study is to examine the effect of transformational leadership style on employee job satisfaction through employee empowerment as a mediating variable. The number of samples taken were 52 employees of DevinSky Hotel Seminyak who had worked for at least 3 years. The sampling technique used in this study is a saturated sampling technique. Data was collected through questionnaires. The analysis technique used is Partial Least Square (PLS). On the results of the analysis it was found that the transformational leadership style variable had a significant positive effect on employee satisfaction at DevinSky Hotel Seminyak, the transformational leadership style variable had a significant positive effect on employee empowerment, the employee empowerment variable had a significant positive effect on employee job satisfaction, employee empowerment mediated the effect of transformational leadership style to the job satisfaction of DevinSky Hotel Seminyak employees. Keywords: transformational leadership style, employee empowerment, job satisfaction.